2021
DOI: 10.3348/kjr.2021.0319
|View full text |Cite
|
Sign up to set email alerts
|

No-Touch vs. Conventional Radiofrequency Ablation Using Twin Internally Cooled Wet Electrodes for Small Hepatocellular Carcinomas: A Randomized Prospective Comparative Study

Abstract: Objective This study aimed to compare the efficacy between no-touch (NT) radiofrequency ablation (RFA) and conventional RFA using twin internally cooled wet (TICW) electrodes in the bipolar mode for the treatment of small hepatocellular carcinomas (HCC). Materials and Methods In this single-center, two-arm, parallel-group, prospective randomized controlled study, we performed a 1:1 random allocation of eligible patients with HCCs to receive NT-RFA or conventional RFA be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…It showed a lower LTP rate compared to conventional tumor-puncturing RFA. 507,508 A prospective multicenter study also found improved local tumor control after no-touch RFA for HCC. 509 However, further investigation is warranted to evaluate whether no-touch RFA would also enhance the survival outcomes after treating pa-tients with HCCs.…”
Section: Local Ablation Therapiesmentioning
confidence: 97%
“…It showed a lower LTP rate compared to conventional tumor-puncturing RFA. 507,508 A prospective multicenter study also found improved local tumor control after no-touch RFA for HCC. 509 However, further investigation is warranted to evaluate whether no-touch RFA would also enhance the survival outcomes after treating pa-tients with HCCs.…”
Section: Local Ablation Therapiesmentioning
confidence: 97%
“…First, as there are two electrodes with adjustable active tip lengths the system can be used for no-touch ablation. Several recent studies have demonstrated better local tumor control of liver malignancies with this approach than conventional tumor puncture techniques, either through percutaneous or laparoscopic approaches [ 27 28 29 ]. Second, since the active tips of the two electrodes are adjustable from 1 cm to 3 cm with a 5 mm step variable, Octopus MP electrodes could be useful in treating asymmetric and ovoid-shaped tumors, especially those with variable diameters that require active tips of different lengths.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tumor feeding and draining vessels are destroyed in the earlier period of RFA, preventing tumor spread via the blood vessels. In two recent RCTs and a prospective multicenter clinical trial, compared with conventional tumor-puncturing RFA, no-touch RFA provided a lower LTP rate [ 24 25 26 ]. However, further investigation is warranted to evaluate whether no-touch RFA enhances survival outcomes after treating patients with small HCCs.…”
Section: Rfamentioning
confidence: 99%